Effects of exergames on mood and cognition in healthy older adults: A randomized pilot study - Moret, Beatrice; Nucci, Massimo; Campana, Gianluca (Frontiers in Psychology, 2022)
The elderly population is increasing and the implementation of stimulating training to promote active aging has become a research issue. This study aimed at investigating the effects of a cognitive-motor exergame training on cognitive functions and mood, in healthy older adults. A randomised controlled pilot study was conducted to compare a cognitive-motor exergame training with a passive control group. The training consisted of 8 sessions of 45 minutes each, including 10 interactive activities focused on several cognitive functions such as memory, processing speed and executive functions, all requiring motor planning and execution. A total of fifty-seven participants were administered a battery of cognitive tests before and after the training. A mixed-effect ANOVA with group (experimental vs control) as between factor and time (pre- and post-test) as within factor, was performed to evaluate the effect of the exergame training on cognitive abilities and mood. Results showed significant interaction effects in processing speed (STROOPC: F (1,53.4) = 9.04, p =.004, R2 =0.82), inhibition (3backs’ false alarms: F (1,47.5) = 5.5, p =.02, R2 = 0.79), and mood (BDI: F (1,55) = 4.15, p =.04, R2 =0.6). Even though post-hoc analyses did not provide statistical evidence supporting the interactions, overall data showed a trend toward better scores only for the experimental group, suggesting a potential improvement in information processing speed, working memory and mood. Exergaming may be a motivating and enjoyable approach to healthy and active aging.